Comparative Evaluation of Sri Lanka Tall and Dwarf x Tall Coconut Hybrids for Tolerance to Weligama Coconut Leaf Wilt Disease in Sri Lanka - Perera, S. A. C. N.; Waidyarathne, K. P.; Dissanayaka, H. D. M. A. C.; Nainanayake, N. P. A. D.; Ekanayake, G. K. (International Coconut Community Journal, 2016)
Weligama Coconut Leaf Wilt Disease (WCLWD) is a phytoplasma disease found in Southern Sri Lanka. It is an incurable, debilitating disease resulting in yield loss and ultimate death of the palm and over 250,000 palms have been identified to be infected. Breeding coconuts for resistance is a viable option in managing incurable diseases and for this WCLWD resistant germplasm is needed. Accordingly, the objective of the current research was to investigate the comparable levels of WCLWD resistance of Sri Lanka tall and CRIC65 coconut cultivars which are favoured in Sri Lanka. Eight coconut estates which were planted with Sri Lanka tall (SLT) and CRIC65 hybrids as a mixed plantation or in close proximity were observed. Out of them an extent of about 04 acres of one estate was selected for detailed analysis using the disease severity index developed based on the WCLWD symptoms; flaccidity, leaf yellowing and marginal necrosis of leaflets. General observations indicated the presence of WCLWD in both SLT and the hybrid CRIC65. Marginal necrosis was at a minimal level in both the cultivars, while the other symptoms; flaccidity and yellowing scored higher values at all levels in the spiral in SLT than in hybrid CRIC65. Moreover, the hybrid coconut CRIC65 displayed lower percentage of disease incidence and significant reduction in the levels of the main symptom flaccidity. As a result, the hybrid palms recorded significantly low disease index value than SLT. Moreover, disease incidence was observed to be low in properly managed estates irrespective of the cultivar. With the findings of the current study, coconut varieties SLGD and selected SLT which remain healthy under the same disease pressure can be recommended as parents in a breeding programme aiming at resistance/tolerance to WCLWD.